GIS Based Modelling of Soil Erosion in Panjkora River Basin Using Revised Universal Soil Loss Equation (RUSLE) - Ahmed, Uzair; Khalil, Fazli Amin; Muhammad Kaleem; Khan, Zahid (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
Research work was conducted to identify the effect of soil errosion on agriculture practices in Panjkora river basin, Khyber Pakhtunkhwa, Pakistan. It is situated in the Eastern Hindu Kush mountain of Pakistan, with an area of 5905 km2. Geo-informatics strategies (GIS) and Revised Universal Soil Loss Equation (RUSLE) were collectively applied to investigate soil degredation. The outcomes reveal that the R factor was in the range of 38.83 to 111.9 MJ mm/ha/h/year, with the minimum values in the Southeastern part, and maximum values in the northern-western part of the basin. For the entire basin, the Topographic Factor (LS) went from 1.34 to 31.20. Besides, the precarious developed slopes are isolated by groove-formed valleys and fundamentally contribute to the sediment supply in the Panjkora River Basin. The review confirms that a high pace of erosion (1-5 ton/ha/yr) is found near the riverbank which reveals that water caused excessive erosion, adversely affecting the land productivity in the agricultural area. It is suggested that viable management methodologies such as terracing, and stream banks stablization are necessary, to decrease the erosion rate in the area where the people mainly relied on agricultural activities for their livelihood.